2017
DOI: 10.5301/jbm.5000224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD24 and CD44 in Breast Cancer: A Meta-Analysis

Abstract: Our study demonstrated that the putative stem cell marker CD24 was significantly associated with worse survival based on the obtained data. In particular, CD24 may play a role in tumorigenesis and cancer progression. However, further large-scale studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 36 publications
(53 reference statements)
3
39
2
1
Order By: Relevance
“…To date, only the particular variant CD44v6 was found to be related to aggressive tumor behavior and prognosis in breast cancer. 31 , 35 This meta-analysis revealed that CD44v6 expression was associated with histological grade, lymph node metastasis, and poor prognosis in breast cancer. CD44v6 also has great implications for targeted therapy and prognostic imaging.…”
Section: Discussionmentioning
confidence: 96%
“…To date, only the particular variant CD44v6 was found to be related to aggressive tumor behavior and prognosis in breast cancer. 31 , 35 This meta-analysis revealed that CD44v6 expression was associated with histological grade, lymph node metastasis, and poor prognosis in breast cancer. CD44v6 also has great implications for targeted therapy and prognostic imaging.…”
Section: Discussionmentioning
confidence: 96%
“…However, CD24 expression can also confer adhesive properties enabling invasion. In a meta-analysis of 16 studies of 5,697 breast cancers, CD24 was found to be signi cantly associated with poorer survival [90], presumably due to non EMP functions. In studies on breast cancer cell lines in vivo, CD24 was found to act as a ligand for P-selectin on the lung vascular endothelium [64].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CD24 overexpression has been correlated with shorter patient survival in breast cancer, ovarian cancer, non-small cell lung carcinomas, prostate tumors, colorectal cancer, and in esophageal squamous cell carcinoma (Kristiansen et al, 2002, 2003, 2004a; Choi et al, 2005; Sano et al, 2009; Majores et al, 2015; Wang et al, 2016). CD24 expression has also been associated with bladder tumor recurrence (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%